133 Effects of Benzoic Acid and Sodium Benzoate Supplementation on Growth Performance of Nursery Pigs. (12th April 2022) - Choi, Hyunjun; Chen, Ying; Longo, Flavio; Kim, Sung Woo
Abstract: This study was to investigate the effects of dietary supplementation of benzoic acid and sodium benzoate on growth performance of nursery pigs. A total of 432 pigs (6.9 ± 0.9 kg BW) were assigned to 8 treatments (6 pigs/pen, n = 9) in a randomized complete block design with initial BW as a block and fed for 41 d in 3 phases (7/17/17 d, respectively). Treatments were 1) basal diet (BD), 2) BD + antibiotic, 3) BD + 0.30% sodium benzoate, 4) BD + 0.40% sodium benzoate, 5) BD + 0.60% sodium benzoate, 6) BD + 0.25% benzoic acid, 7) BD + 0.35% benzoic acid, and 8) BD + 0.50% benzoic acid. Diets contained nutrients meeting the requirement. Growth performance and fecal score were measured for each phase. Pigs representing each pen were euthanized to collect stomach and intestinal digesta to measure pH, and urine to measure pH and hippuric acid content. Data were analyzed using contrasts in Proc MIXED and slope ratio in Proc GLM of SAS. Increasing supplemental sodium benzoate showed a quadratic response ( P < 0.05, max at 339 g/d) on ADG and linear increase ( P < 0.05, 514 to 578 g/d) in ADFI. Increasing supplemental benzoic acid tended to have a quadratic response on ADG ( P = 0.094, max at 323 g/d), but no difference in ADFI. Urine pH linearly decreased ( P < 0.05, 7.5 to 5.7) with increasing supplemental benzoic acid, but was not affected by supplemental sodium benzoate. Increasing both supplemental sodium benzoate and benzoic acid linearly increased ( P < 0.05) hippuric acid content in urine (3.0 to 10.4 and 3.0 to 9.2 g/L, respectively). With the slope-ratio assay using ADG and urine hippuric acid as dependent variables and benzoic acid intake as an independent variable, the estimates of bioavailability of benzoic acids were not different between sources. In conclusion, supplementation of sodium benzoate and benzoic acid increased growth performance without differences in efficacy between the sources.